Isotopic evidence for long-distance connections of the AD thirteenth century Promontory caves occupants - Metcalfe, Jessica Z.; Ives, John W.; Shirazi, Sabrina; Gilmore, Kevin P.; Hallson, Jennifer; Brock, Fiona; Clark, Bonnie J.; Shapiro, Beth (Cambridge University Press, 2021)
The Promontory caves (Utah) and Franktown Cave (Colorado) contain high-fidelity records of short-term occupations by groups with material culture connections to the Subarctic/Northern Plains. This research uses Promontory and Franktown bison dung, hair, hide, and bone collagen to establish local baseline carbon isotopic variability and identify leather from a distant source. The ankle wrap of one Promontory Cave 1 moccasin had a δ13C value that indicates a substantial C4 component to the animal's diet, unlike the C3 diets inferred from 171 other Promontory and northern Utah bison samples. We draw on a unique combination of multitissue isotopic analysis, carbon isoscapes, ancient DNA (species and sex identification), tissue turnover rates, archaeological contexts, and bison ecology to show that the high δ13C value was not likely a result of local plant consumption, bison mobility, or trade. Instead, the bison hide was likely acquired via long-distance travel to/from an area of abundant C4 grasses far to the south or east. Expansive landscape knowledge gained through long-distance associations would have allowed Promontory caves inhabitants to make well-informed decisions about directions and routes of movement for a territorial shift, which seems to have occurred in the late thirteenth century.
Las cuevas Promontory (Utah) y la Cueva Franktown (Colorado) contienen registros de alta fidelidad en cuanto a las ocupaciones de corto término de grupos humanos con cultura material conectada al Subártico/Planicies del Norte. Esta investigación utiliza excremento, pelo, piel de cuero y colágeno del hueso de bisonte provenientes de los sitios Promontory y Franktown para establecer una base de datos isotópicos locales y variabilidad isotópica de carbono e identifica la piel de cuero de procedencia lejana. La envoltura de tobillo de un mocasín recuperado de la Cueva 1 de Promontory tuvo un valor δ13C que indica un componente C4 considerable en la dieta del animal, lo que es un resultado distinto a las dietas C3 que se identificaron a partir del análisis de 171 muestras de bisonte provenientes de Promontory y el norte de Utah. Aplicamos una combinación única de análisis isotópico de tejidos múltiples, mapas isotópicos (“isoscapes”) de carbono, ADN antiguo (identificación de sexo y especie), tasa de remodelación de tejidos, contextos arqueológicos y la ecología del bisonte para demonstrar que el valor alto δ13C probablemente no es un resultado debido al consumo de plantas locales, movilidad del bisonte o comercio. En cambio, la piel de cuero del bisonte fue probablemente adquirida a través de viajes de larga distancia hacia zonas con pastos C4 abundantes muy al sur o al este. El conocimiento extenso sobre el paisaje obtenido a través de asociaciones de larga distancia debió permitir a los habitantes de las cuevas Promontory tomar decisiones bien informadas sobre las direcciones y rutas de movimiento para realizar un cambio territorial, el cual parece haber ocurrido a finales del sigo XIII.
Keywords: stable isotopes; migration; mobility; bison; Great Basin; Promontory Caves; Franktown Cave; Dene; Athapaskan; Apachean; isótopos estables; migración; movilidad; bisonte; Gran Cuenca; Cuevas Promontory; Cueva Franktown; Dene; Atapascano; Apacheano